Enhancement of systemic and sputum granulocyte response to inhaled endotoxin in people with the GSTM1 null genotype. Issue 10 (25th March 2011) - Dillon, Madeline A; Harris, Bradford; Hernandez, Michelle L; Zou, Baiming; Reed, William; Bromberg, Philip A; Devlin, Robert B; Diaz-Sanchez, David; Kleeberger, Steven; Zhou, Haibo; Lay, John C; Alexis, Neil E; et al.
Abstract : Objective: To determine if the GSTM1 null genotype is a risk factor for increased inflammatory response to inhaled endotoxin. Methods: 35 volunteers who had undergone inhalation challenge with a 20 000 endotoxin unit dose of Clinical Center Reference Endotoxin (CCRE) were genotyped for the GSTM1 null polymorphism. Parameters of airway and systemic inflammation observed before and after challenge were compared in GSTM1 null (n=17) and GSTM1 (n=18) sufficient volunteers. Results: GSTM1 null volunteers had significantly increased circulating white blood cells (WBCs), polymorphonuclear neutrophils (PMNs), platelets and sputum PMNs (% sputum PMNs and PMNs/mg sputum) after CCRE challenge. GSTM1 sufficient volunteers had significant, but lower increases in circulating WBCs, PMNs and % sputum PMNs, and no increase in platelets or PMNs/mg sputum. Linear regression analysis adjusted for baseline values of the entire cohort revealed that the GSTM1 null genotype significantly increased circulating WBCs, platelets and % sputum PMNs after challenge. Conclusion: These data support the hypothesis that the GSTM1 null genotype is a risk factor for increased acute respiratory and systemic inflammatory response to inhaled CCRE. These data are consistent with other observations that the GSTM1 null genotype is associated with increased respiratory, systemic and cardiovascular effects linked to ambient air particulate matter exposure and indicate that the GSTM1 null genotype should be considered a risk factor for adverse health effects associated with exposure to environmental endotoxin.